PENINGKATAN PENGETAHUAN TENTANG NUTRISI IBU NIFAS MENGGUNAKAN MEDIA APLIKASI â€œSINNIAâ€ DI RUMAH SAKITAURA SYIFA KEDIRI - Rahajeng Siti Nur Rahmawati; Suwoyo Suwoyo; Sinnia Fauziah Putri (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
The Lack of knowledge of mothers about the nutrition of childbirth mothers, causing the existence of understanding tarak. Smartphones equipped with the application